PROBLEM POSING LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Lina Marlina; Udi Hamzah (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2019)
The research problem of this classroom action research is the low achievement to learn civics class XA SMA AL-Husen City of Tunjung Teja in the academic year 2017. The purpose of this research is to increase the students’ achievement on the subjects of civic education. The results of this research for the school is to improve the quality of civic education, besides that it is also useful for teachers and students. By doing classroom action research the teachers get experience in conducting the learning more interesting and enjoyable. This research implemented in three cycles, where each cycle includes the activities of planning, action, observation and reflection. The Subjects of the research are students of class XA as many as 28 students. The troubleshooting method used is to apply model problem posing learning on the subjects of civic education, the instruments of the research is using observation sheet increase student achievement. Implementation of the research conducted collaboratively with teachers as implementers and researchers act as an observer. The results of this research shows increased student achievement. The cycle I with an average of 53,58. The cycle II with an average 61,76. The cycle III with an average 80,26 Therefore this classroom action research is successful so the researchers recommended the implementation of model problem posing learning can be increasing the students’ learning outcomes on the subjects of civic education.